Impact of manufactured goods’ exports on economic growth: a dynamic econometric model for Nigeria (2004)
The impact of exports on growth has for a long time enmeshed in controversy partly due to both positive and negative effects empirically established in the literature. Still, most studies in developing countries have left detailed examination of exports' components and domestic institutions unexplored in the export-growth nexus. Based on an error correction model, this paper examines the impact of manufactured exports and its components on economic growth in Nigeria, taking cognisance of the country’s institutional framework. Few of the components of manufactured exports were found to exert positive influence on growth both in the long and short runs. The paper, however, finds ample evidence in support of the relevance of quality of institutions in the economic growth process. In effect, with the right institutional framework, export-led growth, , and specific focus on selected manufacturing subsectors there appears to be a feasible development strategy for Nigeria.